Degradation of Phytophysiognomies of Cerrado and linear water erosive impacts in southwest of Goiás – Brazil - Nunes, Elizon Dias; Castro, Selma Simões (Sociedade & Natureza, 2021)
Changes in soil cover and use have become a leading environmental degradation factor, especially soil erosion. In the last four decades, Cerrado environments have undergone an intense conversion to anthropic use, especially agriculture, bare soil and, mainly, pasture. This work evaluates the relationship between these changes and water erosion, highlighting the most affected phytophysiognomies and the consequent emergence of critically degraded areas. The methodology comprises the correlation between the CP factor dynamics (Land cover and use and management practices) of each phytophysiognomy class and land use from 1985 to 2014 and the density of outbreaks and area of erosive contribution in 2014. The results indicate that the period 1985-1995 was noteworthy for converting Savannah, Thin Savanna, and Typical Savanna to Agriculture, Bare Soil and Pasture, while the period 1995-2005, consolidated this type of use. In 2005-2014 there was a low conversion of phytophysiognomies and consequently increased consolidation by anthropic use. The areas with a high density of up to 3.5/km², a high percentage of erosive contribution (up to 48%), and in critical stages of degradation are associated with converting these three phytophysiognomies to Bare Soil and mainly Pasture, both of high CP values. Throughout the period, 53.32 % of the erosive contribution area was due to the same type of conversion. Another 33.88 % occurred in areas where similar use already prevailed in 1985 and persisted in this condition all through the analyzed period.